Second Language Students' Revision During Translating Medical and Literary Texts: A Psycholinguistics Perspective - Ахууд Свар; Мохаммед Мохсен (Психолінгвістика, 2023)
Introduction. Cognitive processes have been extensively examined in the literature of translation studies to identify what goes on in students’ minds when they translate from one language into another. Such investigations targeted translators’ pauses over different texts from their native language into a foreign language. However, identifying translators’ revisions of different types of text remains sufficiently unexplored in the translation studies literature.